Highly efficient and photostable photonic materials from diiodinated BODIPY laser dyes - Perez-Ojeda Rodriguez, Maria Eugenia; Thivierge, C.; Martin, Virginia; Costela, Angel; Burgess, Kevin; García-Moreno, Inmaculada (Optical Materials Express, 2011)
Highly efficient and photostable laser parameters were observed for the diiodinated BODYPY derivatives 1 - 3 both in liquid phase and incorporated into polymeric matrices. The laser samples were transversely pumped at wavelengths near their absorption maxima (515 and 532 nm) at 5 mJ/pulse and 10 Hz repetition rate; these are conditions that would induce photodegrdation of many laser-active fluors. Under these extreme conditions, the new dyes exhibit laser action from 530 nm to 625 nm with remarkable efficiencies, up to 55% in liquid solutions and 45% in poly(methylmethacrylate), and with high photostability since the laser output remains at the initial level, with no sign of degradation, after 100000 pump pulses in the same position of the sample. The efficiencies and photo stabilities of the new dyes outperform those of one presently commercialized and considered benchmarks over this spectral region (i.e. coumarines, xanthenes, perilendiimides). The enhanced optical properties recorded under drastic laser pumping conditions suggest that these new photonic systems could be outstanding in biophotonic applications like optical microscopy and nanoscopy, since they would allow very long observation times and improved spatial resolution. (C)2011 Optical Society of America